Masticatory Rehabilitation of a Patient With Cleft Lip and Palate Malformation Using a Maxillary Full-Arch Reconstruction With a Prefabricated Fibula Flap - Nkenke, Emeka; Vairaktaris, Elefterios; Schlittenbauer, Tilo; Eitner, Stephan (Cleft Palate-Craniofacial Journal, 2016)
For full-arch reconstruction of an atrophied cleft maxilla with missing premaxilla, a prefabricated microvascular free bony flap is a relevant option. A fibula flap was prefabricated in a cleft patient who received six dental implants and an epithelial layer. Six weeks later, maxillary reconstruction was performed. The inpatient period could be confined to 2 weeks. A fixed provisional prosthesis was delivered after an additional 2 weeks. A prefabricated flap allows for the reduction of the interval without a dental prosthesis to only a few weeks, even when a complex full-arch reconstruction of the maxilla is required.
EVALuna2:24418